Pokarm zimowy sowy uszatej (Asio otus) w Busku-Zdroju. - Łagosz, Katarzyna
This thesis concerns research on the composition of the winter food the Long – eared Owl Asio otus in the Busko – Zdrój in two winter seasons: 2009/2010 and 2010/2011. The research used the phenomenon of the annual, winter concentrations of birds in one place, which allows to obtain a substantial amount of research material. The composition of the winter diet was based on analysis of pellets or undigested food debris eaten by a bird. Collected pellets were soaked in water, then dissected the skull, jaw small mammals and remains of birds bones. On the basis of the characteristic series of teeth of mammals were identified to species. It was found during both seasons of research, that the dominant component of the food Long - eared Owl was a Common Vole Microtus arvalis. In the 2009/2010 season Common Vole share in the owl diet was 84.7%, while 2010/2011 season - 40.6%. Among the victims were also found the Striped Field Mouse Apodemus agrarius and Long-tailed Field Mouse Apodemus sylvaticus. Research conducted in Busko-Zdroj confirmed the Long – eared Owl food specialties. The most preferred species is the Common Vole, in the case of reduced availability of owl supplement their diet with other species of the victims. Through this research better understood local fauna of small mammals, and obtained data to the design of "Atlas of Polish Mammals. " Praca dotyczy badań składu pokarmu zimowego sowy uszatej (Asio otus) na stanowisku w Busku-Zdroju w dwóch sezonach zimowych: 2009/2010 i 2010/2011. W badaniach wykorzystano zjawisko corocznej, zimowej koncentracji ptaków w jednym miejscu, co pozwala na uzyskanie znacznej ilości materiału badawczego . Skład pokarmu zimowego określono na podstawie analizy wypluwek, czyli niestrawionych resztek pokarmu zjadanego przez ptaka. Zebrane wypluwki moczono w wodzie, po czym wypreparowywano czaszki i żuchwy drobnych ssaków oraz resztki kostne ptaków. Na podstawie charakterystycznych szeregów zębowych ssaków dokonano identyfikacji osobników co do gatunku. Stwierdzono, podczas obydwu sezonów badawczych, że dominującym składnikiem pokarmu sowy uszatej był nornik zwyczajny (Microtus arvalis). W sezonie 2009/2010 udział nornika zwyczajnego w pokarmie sowy wyniósł 84,7%, natomiast w sezonie 2010/2011– 40,6%. Wśród ofiar znaleziono również mysz polną (Apodemus agrarius) oraz mysz zaroślowa (Apodemus sylvaticus). Badania prowadzone na stanowisku w Busku-Zdroju potwierdziły specjalizacje pokarmową sowy uszatej. Najbardziej preferowanym gatunkiem jest nornik zwyczajny, a w przypadku jego mniejszej dostępności sowa uzupełnia swoją dietę innymi gatunkami ofiar. Dzięki tym badaniom lepiej poznano lokalną faunę drobnych ssaków i uzyskano dane do opracowywanego „Atlasu ssaków Polski”.